2005
DOI: 10.1523/jneurosci.3362-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

GABAAReceptor-Mediated Tonic Inhibition in Thalamic Neurons

Abstract: Tonic GABA A receptor-mediated inhibition is typically generated by ␦ subunit-containing extrasynaptic receptors. Because the ␦ subunit is highly expressed in the thalamus, we tested whether thalamocortical (TC) neurons of the dorsal lateral geniculate nucleus (dLGN) and ventrobasal complex exhibit tonic inhibition. Focal application of gabazine (GBZ) (50 M) revealed the presence of a 20 pA tonic current in 75 and 63% of TC neurons from both nuclei, respectively. No tonic current was observed in GABAergic neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
342
3
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(379 citation statements)
references
References 60 publications
(112 reference statements)
33
342
3
1
Order By: Relevance
“…In this way, tonic inhibition on LTS cells would be an extrinsic, rather than intrinsic, regulator. This role of tonic inhibition in the cortex favoring slow wave activity associated with sleep fits with tonic inhibition in the thalamus promoting bursting and slow-wave activity (Belelli et al, 2005;Cope et al, 2005). With regard to this hypothesis, it is of interest whether FS cells have the same degree of tonic GABA A -mediated inhibition as LTS cells.…”
Section: From Steriade To the Futurementioning
confidence: 90%
“…In this way, tonic inhibition on LTS cells would be an extrinsic, rather than intrinsic, regulator. This role of tonic inhibition in the cortex favoring slow wave activity associated with sleep fits with tonic inhibition in the thalamus promoting bursting and slow-wave activity (Belelli et al, 2005;Cope et al, 2005). With regard to this hypothesis, it is of interest whether FS cells have the same degree of tonic GABA A -mediated inhibition as LTS cells.…”
Section: From Steriade To the Futurementioning
confidence: 90%
“…During the last decade, several studies have shown that GABA A receptor activation can also mediate tonic inhibition; these receptors are extrasynaptically and perisynaptically localized and contain a distinct, high affinity subunit composition made of δ and α4, α5 & α6 subunits (Nusser et al, 1998;Yeung et al, 2003;Semyanov et al, 2003Semyanov et al, , 2004Cope et al, 2005;Scimemi et al, 2005;Glykys et al, 2008). Hence, GABA A receptors can generate two types of current, depending on their location and subunit composition: the first type is the classic synaptic phasic (or 'transient') current that results from the release of GABA from synaptic vesicles in the synaptic cleft; the second type is a tonic ('always on') current that is caused by GABA A receptors responding to low levels of ambient GABA (Farrant and Nusser, 2005).…”
Section: Gaba a Receptor-mediated Tonic Inhibitionmentioning
confidence: 99%
“…So far, it is not known whether this complex regulation of tonic inhibition is related to the heterogeneity of extrasynaptic GABA A receptors in granule cells. However, it should be emphasized that the role of the d subunit is forming receptors mediating tonic inhibition is not restricted to the cerebellum, but also occurs in thalamus and hippocampus (35,36). Furthermore, these receptors Note that Lugaro cells innervate all cell types in the molecular layer except PC.…”
Section: Organization Of Gaba a Receptors In The Cerebellar Cortexmentioning
confidence: 99%